Designing and validation a model of enhancement motivational training program for female students with depressive symptoms - Fouladi, Maryam; Vaziri, Saeed; Fallah, Mohammad Hossein; Afshani, Alireza (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Motivation as a psychological structure is effective in the well-being of a person. Accordingly, lack of motivation affects emotional states. The purpose of the current research is to design and validate the motivation training program in student girls with depression symptoms. Methods: The present research has been done using a qualitative and quantitative mixed research method. In the qualitative part of the research, semi-structured interview has been used. The study population included 11 female students living in Yazd and purposive sampling method used and sampling continued until data saturation and no new data were available. Based on the analysis of the themes, the pattern of enhancement motivation training program was designed, In the quantitative part of the research, For validation and reliability by the content validity of the educational program template of the CVR (Content Validity Ratio) use. Using purposive sampling method, the proposed model was provided to 24 psychologists and the validity of the data was analyzed. Results: The results showed that based on CVR, all 20 main themes in the proposed model were confirmed. Conclusion: In general, it can be acknowledged that the model based on strengthening motivation offers a different perspective in the treatment of depressed patients. Paying attention to the theoretical dimensions of this model and its application in treatment is of special importance.